The Adventures of Tom Sawyer : 135th Anniversary Edition. - Twain, Mark, 1835-1910 (Mark Twain Library., 2010)
This landmark anniversary edition contains a selection of Twain's hard-to-find letters and notes expressing his always-engaging opinions on the publication of Tom Sawyer.